Fly ash-based light-weight autoclaved aerated concrete board and preparation method thereof
Patent Information
- Application Number
- CN202611445316.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]该工艺在实际生产中,坯体能否稳定切割,主要取决于预养阶段形成的早期水化结构,其中普通硅酸盐水泥生成的C-S-H等产物能够把粉煤灰、石灰等颗粒连接起来,也是后续蒸压水热反应的重要前驱体;为了减少坯体在翻转和切割时发生变形、掉角或破损,通常需要提高预养阶段的反应程度,随着早期水化产物不断生成,其结构也会继续发展,进入蒸压阶段后可继续调整和转化的空间随之减小,粉煤灰中的硅铝组分参与后续水热反应也会受到影响;若降低预养阶段的反应程度,坯体又可能达不到切割所需的强度,因此现有技术存在坯体切割强度与蒸压阶段后续水热强化难以兼顾的问题
[0017]本发明中,通过在粉煤灰、生石灰和普通硅酸盐水泥形成主体料浆后,再加入硫铝酸盐熟料和二水石膏,并同时加入三乙醇胺,使硫铝酸盐水化产物在预养阶段参与绿坯早期结构的形成,同时调节复合料浆的反应速度,使铝粉膏发气、料浆稠化和绿坯强度增长相互配合,与现有技术相比,本发明不是停止普通硅酸盐水泥的水化,而是由硫铝酸盐水化产物分担部分早期支撑作用,使绿坯在普通硅酸盐水泥反应程度相对较低时达到脱模和切割要求,减少发气后坯体回落或过早稠化的情况,并为蒸压阶段粉煤灰中的硅铝组分与钙质组分继续进行水热反应保留条件,从而使制得的板材在保持轻质和保温性能的同时具有较好的强度及体积稳定性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic building materials technology, and in particular to fly ash-based lightweight thermal insulation autoclaved aerated concrete panels and their preparation methods. Background Technology
[0002] Autoclaved aerated concrete (AAC) panels typically use siliceous materials such as fly ash, quicklime, and calcareous materials such as cement as the main raw materials. Gypsum, aluminum powder paste, and water are added to form a slurry. The aluminum powder paste reacts under alkaline conditions to produce gas, causing the slurry to expand and form a porous blank. Subsequently, pre-curing promotes early reactions of components such as cement and lime, gradually shaping the pore walls and enabling demolding, turning, and cutting. The cut blank is then sent to an autoclave, where the silica and aluminum components in the fly ash continue to react with the calcareous components under high temperature and high pressure steam conditions, forming the final pore wall cemented structure of the panel.
[0003] Chinese patent application CN109650802A discloses an aerated concrete panel and its manufacturing process, using fly ash, cement, lime, phosphogypsum, and aluminum powder as raw materials, and producing panels through mixing, pouring, initial curing, demolding, cutting, and autoclaving. Chinese patent application CN108585653A discloses an autoclaved aerated concrete panel and its molding process, using fly ash, cement, quicklime, and aerated aluminum paste to prepare a slurry, which is then statically cured, cut, and autoclaved to form panels. Both processes require the pre-cured aerated body to reach the strength required for cutting, and then autoclaving is used to further strengthen the pore wall structure of the panel.
[0004] In actual production, the stability of the green body during cutting depends primarily on the early hydration structure formed during the pre-curing stage. Products such as CSH generated from ordinary silicate cement connect fly ash and lime particles, serving as important precursors for subsequent autoclaving hydrothermal reactions. To reduce deformation, chipping, or breakage of the green body during turning and cutting, the reaction intensity during the pre-curing stage is typically increased. As early hydration products continue to form, their structure evolves, reducing the space for further adjustment and transformation during the autoclaving stage. The participation of silica-alumina components in fly ash in subsequent hydrothermal reactions is also affected. Conversely, reducing the reaction intensity during the pre-curing stage may result in the green body failing to reach the required cutting strength. Therefore, existing technologies suffer from a dilemma: achieving both sufficient cutting strength and adequate hydrothermal enhancement during the autoclaving stage is difficult. Summary of the Invention
[0005] The technical problem to be solved by this invention is that the cutting strength of the existing blank mainly depends on the early hydration of ordinary silicate cement, which makes it difficult to balance the formation of cutting strength in the pre-curing stage with the subsequent hydrothermal strengthening in the autoclaving stage. To this end, we propose a fly ash-based lightweight thermal insulation autoclaved aerated concrete panel and its preparation method.
[0006] To achieve the above objectives, this application adopts the following technical solution: a method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels, comprising the following steps: S1: mixing fly ash with water to obtain fly ash slurry; S2: adding quicklime, ordinary silicate cement, and water to the fly ash slurry and mixing to obtain a main slurry; S3: pre-dry mixing sulfoaluminate clinker with gypsum, and after the main slurry is formed, adding the obtained mixture to the main slurry, and simultaneously adding triethanolamine aqueous solution and mixing, wherein the triethanolamine is added according to the effective... The amount of triethanolamine used is 0.20%-0.45% of the total mass of ordinary silicate cement and sulfoaluminate clinker; S4: Mix aluminum powder paste with water to prepare aluminum powder paste dispersion. After mixing in step S3, add the aluminum powder paste dispersion to the slurry obtained in step S3, mix, and pour into the mold; S5: Pre-cur the poured slurry. When the compressive strength of the green billet reaches 0.30 MPa, demold and cut to obtain the board blank; S6: Autoclave the board blank, remove it from the autoclave and cool it to obtain the finished product.
[0007] Preferably, in step S1, fly ash and water are stirred at 600 r / min for 15 min to obtain fly ash slurry with a solid content of 56%-60%.
[0008] Preferably, in step S2, quicklime, ordinary silicate cement and water are added to the fly ash slurry and mixed at 900 r / min to obtain a main slurry with a temperature of 40-42℃ and a solid content of 62%-63%.
[0009] Preferably, in step S3, the triethanolamine aqueous solution has a mass fraction of 10%, which is obtained by diluting an 85% triethanolamine aqueous solution with water.
[0010] Preferably, in step S4, aluminum powder paste and water are mixed at a mass ratio of 1:10 and stirred at 300 r / min for 2 min to obtain an aluminum powder paste dispersion.
[0011] Preferably, after the temperature of the slurry obtained in step S3 reaches 42±1℃, aluminum powder paste dispersion is added and mixed at 600r / min. Then the resulting slurry is poured into the mold, and the initial pouring height is 53%-57% of the effective height of the mold.
[0012] Preferably, in step S6, the plate blanks are grouped and sent into an autoclave, steam is introduced to replace the air in the autoclave, the temperature inside the autoclave is raised to 190±2℃ within 2 hours, and the gauge pressure inside the autoclave is controlled at 1.15-1.25MPa. The temperature and pressure are maintained for 7 hours, and then the pressure is reduced to atmospheric pressure within 2 hours. After the surface temperature of the product drops below 60℃, it is removed from the autoclave, separated, and naturally cooled to room temperature.
[0013] A fly ash-based lightweight thermal insulation autoclaved aerated concrete panel, wherein the raw materials of the panel, based on a dry basis of 100 parts, include 69.3-70.7 parts fly ash, 16.5 parts quicklime, 8.0-9.2 parts ordinary Portland cement, 0.8-2.0 parts sulfoaluminate clinker and 2.8-4.2 parts dihydrate gypsum.
[0014] Preferably, the raw materials for the sheet also include aluminum powder paste, the amount of which is calculated based on active aluminum, and the amount of active aluminum is 0.063% of the total dry basis.
[0015] Preferably, the dry bulk density of the board is 504-524 kg / m³. 3 Its compressive strength is 3.91-4.34 MPa, and its thermal conductivity is 0.117-0.122 W / (m·K).
[0016] The technical effects and advantages of this invention are as follows:
[0017] In this invention, after fly ash, quicklime, and ordinary silicate cement form the main slurry, sulfoaluminate clinker and gypsum dihydrate are added, along with triethanolamine. This allows the sulfoaluminate hydration products to participate in the early structure formation of the green blank during the pre-curing stage. Simultaneously, the reaction rate of the composite slurry is adjusted, ensuring that the gas generation of aluminum powder paste, slurry thickening, and green blank strength increase work in tandem. Compared to existing technologies, this invention does not stop the hydration of ordinary silicate cement; instead, the sulfoaluminate hydration products share some of the early support role. This allows the green blank to meet demolding and cutting requirements when the reaction degree of ordinary silicate cement is relatively low, reducing the possibility of the green blank falling back or thickening prematurely after gas generation. Furthermore, it preserves the conditions for the continued hydrothermal reaction between the silica-alumina components and calcium components in the fly ash during the autoclaving stage. Therefore, the resulting board maintains its lightweight and thermal insulation properties while possessing good strength and volume stability. Attached Figure Description
[0018] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings:
[0019] Figure 1 The XRD patterns of the green blanks of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5 when they reached the cutting state;
[0020] Figure 2 The isothermal calorimetric cumulative heat release curves for Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 5 are shown.
[0021] Figure 3 The XRD patterns are of the autoclaved products obtained in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5. Detailed Implementation
[0022] All raw materials used in the specific implementation method are from the same batch. Unless otherwise specified, the raw material specifications, pulping conditions, pouring conditions, pre-curing conditions and autoclaving regime are consistent. The parts mentioned in the formula refer to parts by weight.
[0023] The dosage of fly ash, quicklime, ordinary silicate cement, sulfoaluminate clinker and gypsum is calculated on a dry basis. The actual weighing amount is converted according to the measured moisture content of the raw materials. The water introduced by the raw materials and the water added during the pulping process are included in the total water consumption.
[0024] The fly ash used is low-calcium fly ash, with a sieve residue of 14.6% on a 45μm square hole sieve, a loss on ignition of 3.1%, and a moisture content of 0.4%. By mass percentage, the fly ash contains 51.8% SiO2, 27.6% Al2O3, and 5.3% CaO.
[0025] The quicklime used has an effective CaO content of 83.2% and an MgO content of 3.4%. The digestion time is 8 minutes and the maximum digestion temperature is 79℃. Before use, the quicklime is crushed and passed through a 0.15mm sieve.
[0026] The ordinary Portland cement used was P·O 42.5 cement, with an initial setting time of 176 min, a final setting time of 231 min, and a specific surface area of 356 m². 2 / kg, the calcium sulfoaluminate clinker contains 57.8% calcium sulfoaluminate minerals, 1.3% free CaO, and has a specific surface area of 405 m². 2 / kg.
[0027] The gypsum used is dihydrate gypsum with a CaSO4·2H2O content of 92.6% and an adhering water content of 3.2%. Before use, it is dried at 45℃ until the adhering water content is ≤0.5%, and then ground and passed through a 0.15mm sieve.
[0028] The triethanolamine used is an 85% triethanolamine aqueous solution. The amount used is based on the effective triethanolamine and the total mass of ordinary silicate cement and sulfoaluminate clinker is used as the calculation basis. Before use, it is diluted with water to a 10% triethanolamine aqueous solution, and the dilution water is included in the total water consumption.
[0029] The aluminum powder paste used is a water-based aluminum powder paste for autoclaved aerated concrete, with a solid content of 70.4% and an active aluminum content of 65.1%. Its dosage is calculated based on the active aluminum content. Before use, the aluminum powder paste is mixed with water at a mass ratio of 1:10 and stirred at 300 r / min for 2 min to obtain an aluminum powder paste dispersion. The dispersion water is included in the total water consumption.
[0030] The steel mesh used is welded from HPB300 steel bars with a diameter of 5mm. The mesh size is 100mm×100mm. After being dipped in water-based epoxy modified anti-corrosion coating, the steel mesh is dried at 80℃ for 30 minutes. The dry film thickness of the anti-corrosion layer is 80-120μm.
[0031] Specific embodiments also provide a method for preparing the fly ash-based lightweight thermal insulation autoclaved aerated concrete panel, which specifically includes the following steps:
[0032] S1: Weigh the fly ash according to the formula, add the fly ash and water to the slurry tank, stir at 600 r / min for 15 min to obtain fly ash slurry with a solid content of 56%-60%, then continue stirring at 120 r / min and adjust the temperature of fly ash slurry to 38±1℃.
[0033] S2: Add fly ash slurry to a casting mixer, then add quicklime, ordinary Portland cement and water, mix at 900 r / min for 75 s to obtain a main slurry with a temperature of 40-42℃ and a solid content of 62%-63%;
[0034] S3: After dry mixing the sulfoaluminate clinker and gypsum for 2 minutes, add the slurry and simultaneously add a 10% (w / w) triethanolamine aqueous solution. Continue mixing at 700 r / min for 30 seconds.
[0035] S4: Fix the two layers of steel mesh in parallel inside the mold. After the slurry temperature reaches 42±1℃, add aluminum powder paste dispersion and mix at 600r / min for 20s. Then pour the slurry into the mold. The initial pouring height is 53%-57% of the effective height of the mold.
[0036] S5: After casting, the mold is moved into a pre-curing chamber with a temperature of 50±2℃ and a relative humidity of ≥90% for pre-curing. When the compressive strength of the green blank reaches 0.30±0.02MPa, it is flipped and demolded, the top cap is cut off, and then longitudinal and transverse cutting is performed in sequence to obtain the plate blank.
[0037] S6: The sheet blanks are grouped and sent into the autoclave. Steam is introduced to replace the air in the autoclave. The temperature inside the autoclave is raised to 190±2℃ within 2 hours. The gauge pressure inside the autoclave is controlled at 1.15-1.25MPa. The temperature and pressure are maintained for 7 hours. Then the pressure is reduced to atmospheric pressure within 2 hours. After the surface temperature of the product drops below 60℃, it is removed from the autoclave, separated, and naturally cooled to room temperature to obtain the finished product.
[0038] The finished products were placed in an environment with a temperature of 20±2℃ and a relative humidity of 50±5% for 7 days before being tested for dry bulk density, compressive strength, thermal conductivity and drying shrinkage. Green blanks used for pre-curing stage testing were sampled separately according to the time and condition specified in the corresponding experimental example, without autoclaving.
[0039] The present invention will be described below through examples and comparative examples. Unless otherwise specified, each example and comparative example was prepared according to the aforementioned preparation method. The specific raw material dosage and adjustment method are as follows. The total water consumption of each group is 58.5 parts.
[0040] Example 1
[0041] In this embodiment, the amounts of fly ash, quicklime, ordinary silicate cement, sulfoaluminate clinker, and dihydrate gypsum are 70.0 parts, 16.5 parts, 8.5 parts, 1.5 parts, and 3.5 parts, respectively. The effective amount of triethanolamine is 0.30% of the total mass of ordinary silicate cement and sulfoaluminate clinker, i.e., 0.03 parts, and the amount of active aluminum is 0.063 parts.
[0042] Fly ash and water were added to a slurry mixing tank and stirred at 600 r / min for 15 min to obtain a fly ash slurry with a solid content of 58.0%. Then, stirring was continued at 120 r / min and the temperature of the fly ash slurry was adjusted to 38℃.
[0043] The obtained fly ash slurry was added to a casting mixer, then quicklime, ordinary Portland cement and water were added, and mixed at 900 r / min. During the mixing process, the slurry temperature rose from 38℃ to 41℃, and the solid content of the main slurry was 62.4%.
[0044] Sulfoaluminate clinker and gypsum dihydrate were dry-mixed for 2 minutes to obtain sulfoaluminate modifier. The sulfoaluminate modifier was added to the main slurry, and triethanolamine aqueous solution was added at the same time. The mixture was then mixed for 30 seconds at 700 r / min.
[0045] Two layers of steel mesh are fixed parallel inside the mold. Aluminum powder paste is mixed with water and stirred at 300 r / min for 2 min to obtain aluminum powder paste dispersion. After the slurry temperature reaches 42℃, aluminum powder paste dispersion is added and mixed at 600 r / min for 20 s. Then the slurry is poured into the mold with an initial pouring height of 55% of the effective height of the mold.
[0046] After casting, the mold is moved into a pre-curing chamber with a temperature of 50℃ and a relative humidity of 92% for pre-curing. After 185 minutes of pre-curing, the compressive strength of the green blank reaches 0.30MPa. Then, the mold is flipped and demolded, the top cap is removed, and then longitudinal and transverse cutting is performed to obtain a plate blank with dimensions of 3000mm×600mm×100mm.
[0047] The slab blanks are grouped and fed into an autoclave. Steam is introduced to replace the air inside the autoclave, and the temperature inside the autoclave is raised to 190℃ within 2 hours. The gauge pressure inside the autoclave is controlled at 1.15-1.25MPa, and the temperature and pressure are maintained for 7 hours. Then, the pressure is reduced to atmospheric pressure within 2 hours. After the surface temperature of the product drops below 60℃, it is removed from the autoclave, separated, and naturally cooled to room temperature to obtain the finished concrete slab.
[0048] Unless otherwise specified, the pre-curing endpoint for each group is the compressive strength of the unreinforced test billets in the same batch reaching 0.30 MPa. The actual pre-curing time is determined based on the strength test results of each group of green billets.
[0049] The difference between Example 2 and Example 1 is that the effective amount of triethanolamine is adjusted to 0.20% of the total mass of ordinary silicate cement and sulfoaluminate clinker, i.e., 0.02 parts. 0.20 parts of a 10% triethanolamine aqueous solution are added to S3. The amount of other raw materials and preparation conditions are the same as in Example 1.
[0050] The difference between Example 3 and Example 1 is that the effective amount of triethanolamine is adjusted to 0.45% of the total mass of ordinary silicate cement and sulfoaluminate clinker, i.e., 0.045 parts. 0.450 parts of a 10% triethanolamine aqueous solution are added to S3. The amount of other raw materials and preparation conditions are the same as in Example 1.
[0051] The difference between Example 4 and Example 1 is that the amounts of ordinary silicate cement and sulfoaluminate clinker are adjusted to 9.2 parts and 0.8 parts, respectively, with the total amount remaining at 10.0 parts. The amount of effective triethanolamine remains at 0.030 parts, while the amounts of other raw materials and preparation conditions are the same as in Example 1.
[0052] The difference between Example 5 and Example 1 is that the amounts of ordinary silicate cement and sulfoaluminate clinker are adjusted to 8.0 parts and 2.0 parts respectively, with the total amount of the two still being 10.0 parts. The amount of effective triethanolamine is still 0.030 parts, and the amounts of other raw materials and preparation conditions are the same as in Example 1.
[0053] The difference between Example 6 and Example 1 is that the amounts of fly ash and gypsum dihydrate are adjusted to 70.7 parts and 2.8 parts, respectively. Fly ash is mixed with water to obtain fly ash slurry with a solid content of 58.0%. The amounts of other raw materials and preparation conditions are the same as in Example 1.
[0054] The difference between Example 7 and Example 1 is that the amounts of fly ash and gypsum dihydrate are adjusted to 69.3 parts and 4.2 parts, respectively. Fly ash is mixed with water to obtain fly ash slurry with a solid content of 58.0%. The amounts of other raw materials and preparation conditions are the same as in Example 1.
[0055] The difference between Comparative Example 1 and Example 1 is that sulfoaluminate clinker and triethanolamine are not added, and 1.5 parts of sulfoaluminate clinker are replaced with an equal mass of ordinary silicate cement, so that the amount of ordinary silicate cement is adjusted to 10.0 parts. In S3, 3.5 parts of dihydrate gypsum and water are added to the main slurry and mixed at 700 r / min for 30 s. The amount of other raw materials and preparation conditions are the same as in Example 1.
[0056] The difference between Comparative Example 2 and Example 1 is that triethanolamine is not added. In step S3, 1.5 parts of sulfoaluminate clinker and 3.5 parts of gypsum dihydrate are dry-mixed for 2 minutes and then added to the main slurry. After adding water, the mixture is mixed at 700 r / min for 30 seconds. The amount of other raw materials and preparation conditions are the same as in Example 1.
[0057] The difference between Comparative Example 3 and Example 1 is that sulfoaluminate clinker is not added, and 1.5 parts of sulfoaluminate clinker are replaced with an equal mass of ordinary silicate cement, so that the amount of ordinary silicate cement is adjusted to 10.0 parts. In S3, 3.5 parts of gypsum dihydrate and triethanolamine aqueous solution are added to the main slurry and mixed at 700 r / min for 30 s. The amount of other raw materials and preparation conditions are the same as in Example 1.
[0058] The difference between Comparative Example 4 and Example 1 is that the timing of adding sulfoaluminate clinker, gypsum dihydrate, and triethanolamine is changed. After adding fly ash slurry to the casting mixer, quicklime, ordinary silicate cement, sulfoaluminate clinker, gypsum dihydrate, triethanolamine aqueous solution, and water are added simultaneously. The mixture is mixed at 900 r / min for 75 s, and then mixed at 700 r / min for 30 s. The remaining preparation conditions are the same as in Example 1.
[0059] The difference between Comparative Example 5 and Example 1 is that the effective amount of triethanolamine was adjusted to 0.60% of the total mass of ordinary silicate cement and sulfoaluminate clinker, i.e., 0.060 parts. In step S3, 0.600 parts of a 10% triethanolamine aqueous solution were added. The remaining raw material amounts and preparation conditions were the same as in Example 1.
[0060] To facilitate comparison of the formulation differences between the various embodiments and comparative examples, the formulation composition of each group is summarized in Table 1. The formulation composition of Comparative Example 4 is the same as that of Example 1. The only difference between the two is the order in which sulfoaluminate clinker, gypsum dihydrate and triethanolamine are added.
[0061] Table 1. Formulation composition of the examples and comparative examples
[0062]
[0063] Experimental verification
[0064] To verify the impact of each formulation and process adjustment on the formation of green blanks and the performance of finished products, the following experiments were conducted on the examples and comparative examples.
[0065] To investigate the gas generation process and green billet strength formation of each slurry group, timing was started after the aluminum powder paste dispersion was added and stirring was completed. The slurries were poured into graduated transparent molds and then placed in a pre-curing chamber at a temperature of 50±2℃ and a relative humidity of ≥90% for pre-curing. Three parallel samples were set up for each group. The time when the slurry started to rise, reached the maximum height, and the time when the height stopped changing for 5 minutes after reaching the maximum height were recorded as the gas generation start time, expansion peak time, and gas generation end time, respectively.
[0066] The expansion rate and the setback rate are calculated based on the initial height, maximum height, and stable height after the gas generation is completed. The expansion rate is the percentage of the difference between the maximum height and the initial height to the initial height, and the setback rate is the percentage of the difference between the maximum height and the stable height to the maximum height.
[0067] Another batch of slurry was used to cast unreinforced test blanks, which were pre-cured simultaneously with the corresponding plate blanks. Cube specimens of the same size were cut at 2h, 3h, and 4h of pre-curing, respectively. The compressive strength of the green blanks was tested at a loading rate of 0.02MPa / s. Three parallel specimens were set up for each group, and the average value was taken. When the compressive strength of the green blanks approached 0.30MPa, the testing frequency was increased. The pre-curing time required for the green blanks to first reach 0.30±0.02MPa was recorded. The test results are shown in Table 2.
[0068] Table 2. Gas generation process and compressive strength of green slurry for each group
[0069]
[0070] As shown in Table 2, the expansion rate of the embodiment is 83.9%-87.6%, the fall rate is 1.6%-3.0%, and the time required to reach the cutting state is 168-214 minutes. This indicates that within the formulation range of the present invention, the slurry can complete sufficient gas generation and maintain a small fall after gas generation, while forming the green blank strength required for cutting during the pre-curing stage.
[0071] The slurry expansion rates of Comparative Examples 1, 3, and 5 were relatively high, but the shrinkage rate increased to 5.8%-9.4%, and the time required for the green green brick to reach a compressive strength of 0.30 MPa was extended to 233-286 min. The green green brick strength formation of Comparative Examples 2 and 4 was faster, but the slurry expansion rates decreased to 79.8% and 78.6%, respectively. This indicates that it is difficult to balance the degree of slurry expansion, the stability after gas generation, and the rate of green green brick strength formation if the reaction rate is too fast or too slow.
[0072] While preparing each group of unreinforced test blanks, phase test blanks were cast separately using the same batch of slurry and pre-cured under conditions of 50±2℃ and relative humidity ≥90%. According to the test results of the green blank compressive strength in Table 2, the sampling time was recorded when the compressive strength of each group of green blanks reached 0.30±0.02MPa, and samples were taken from the center of the corresponding phase test blank.
[0073] The sample was crushed to a particle size ≤5mm and immersed in anhydrous isopropanol at a solid-liquid mass ratio of 1:10 to terminate the hydration reaction. After soaking for 6 hours, the anhydrous isopropanol was replaced and the sample was soaked for another 18 hours. Subsequently, the sample was vacuum dried at 40℃ to constant weight and then ground through a 0.075mm sieve.
[0074] The obtained powder was mixed with 10% α-Al₂O₃ internal standard, and then detected using an X-ray diffractometer. The radiation source was Cu-Kα, the tube voltage was 40 kV, the tube current was 40 mA, the scanning range was 5°–60°, the step size was 0.02°, and the scanning speed was 2° / min. The contents of ettringite, monosulfide hydrated calcium sulfoaluminate, Ca(OH)₂, and residual dihydrate gypsum were calculated using the Rietveld full-spectrum fitting method. Three parallel samples were set up for each group, and the average value of the test results was taken. The XRD patterns of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 5 are shown in [reference needed]. Figure 1 The quantitative results of the main crystalline phases in each group are shown in Table 3.
[0075] Table 3. Content of major crystalline phases when each group reaches the same cutting state.
[0076]
[0077] Based on the phase analysis in Table 3, X-ray diffraction quantitative analysis was performed on ordinary silicate cement and sulfoaluminate clinker from the same batch to determine the initial total content of tricalcium silicate and dicalcium silicate in ordinary silicate cement and the initial content of calcium sulfoaluminate in sulfoaluminate clinker. The reaction rate was calculated based on the residual content of the corresponding minerals when each group of green briquettes reached 0.30±0.02MPa. Among them, the silicate clinker mineral reaction rate is the percentage of the reaction amount of tricalcium silicate and dicalcium silicate to their initial total amount, and the calcium sulfoaluminate reaction rate is the percentage of the reaction amount of calcium sulfoaluminate to its initial content.
[0078] Thermogravimetric analysis was performed on the same batch of dried powder used in the test as shown in Table 3. The temperature was increased from 30℃ to 1000℃ under a nitrogen atmosphere at a heating rate of 10℃ / min and a nitrogen flow rate of 50mL / min. The bound water rate was calculated based on the mass loss in the range of 105-550℃. Three parallel samples were set up for each group, and the average value of the test results was taken.
[0079] Calorimetric samples were prepared in equal proportions according to the formulas of each group, without adding aluminum powder paste, and the total water volume was replenished to 58.5 parts with deionized water. The composition of other raw materials and the order of feeding S1-S3 remained unchanged. The samples were placed in an isothermal calorimeter at a temperature of 50°C. The timing point was taken when the fly ash slurry came into contact with quicklime and ordinary Portland cement. The cumulative heat release at the sampling time in Table 3 was recorded for each group. The cumulative heat release was calculated based on the total mass of the five dry-based raw materials. Three parallel samples were set up for each group and the average value was taken. The cumulative heat release curves of isothermal calorimetry for Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 5 are shown in Table 3. Figure 2 The test results for each group are shown in Table 4.
[0080] Table 4. Reaction extent and hydration exothermic response when each group reaches the same cutting state.
[0081]
[0082] As shown in Tables 3 and 4, when the green blanks reach the same compressive strength, the silicate clinker mineral reaction rate is lower than that of Comparative Examples 1, 3 and 5, the ettringite content is relatively high, and the bound water rate and cumulative heat release are also at a low level. This indicates that the early hydration products formed by sulfoaluminate clinker and dihydrate gypsum can participate in the formation of the green blank structure, enabling the green blank to reach the cutting strength when the silicate clinker reaction degree is low.
[0083] A comparison of Examples 1, 4, and 5 shows that increasing the amount of sulfoaluminate clinker can improve the reaction rate of calcium sulfoaluminate and accelerate the formation of green green strength, but it will cause the slurry to thicken earlier. A comparison of Examples 1, 6, and 7 shows that when the amount of dihydrate gypsum is too low, the content of monosulfate hydrated calcium aluminate increases, and when the amount of dihydrate gypsum is too high, the residual dihydrate gypsum increases and the time for the green green to reach cutting strength is prolonged. Therefore, the amounts of sulfoaluminate clinker and dihydrate gypsum need to be matched.
[0084] Comparative Examples 2 and 4 showed higher calcium sulfoaluminate reaction rates and ettringite content, resulting in faster green green strength formation. However, the slurry expansion rate shown in Table 2 was low, indicating that the premature formation of sulfoaluminate hydration products would limit the continued expansion of the slurry. Comparative Examples 3 and 5 did not include sulfoaluminate clinker, and to achieve the same green green strength, they required higher silicate clinker reaction rates, bound water rates, and cumulative heat release. This suggests that adjusting the amount of triethanolamine alone cannot replace the role of sulfoaluminate clinker and gypsum dihydrate in early structure formation.
[0085] To compare the differences in hydration development when green billets reach the same cutting strength and continue pre-curing, samples from Example 1 and Comparative Example 1 were selected. Two groups of unreinforced test billets were prepared using the same batch of slurry and placed in a pre-curing chamber at a temperature of 50±2℃ and a relative humidity of ≥90% for pre-curing. When the compressive strength of the green billets reached 0.30±0.02MPa, one group was sampled immediately, and the other group was sampled after continuing pre-curing for 60 minutes. The sampling times were recorded and the compressive strength of the green billets was tested.
[0086] Samples were taken from the center of each unreinforced test billet, and the hydration reaction was terminated according to the aforementioned method. The contents of ettringite, monosulfide hydrated calcium aluminate, silicate clinker mineral reaction rate and bound water rate were tested respectively. The cumulative heat release corresponding to the sampling time was read from the isothermal calorimetry curves of each group. Three parallel samples were set for each group and the average value was taken. The test results are shown in Table 5.
[0087] Table 5. Detection results after 60 minutes of pre-curing following reaching the cutting state.
[0088]
[0089] As shown in Table 5, after reaching the cutting state, both Example 1 and Comparative Example 1 continued pre-curing for 60 minutes, and the compressive strength of the green billet increased from 0.30 MPa to 0.42 MPa. However, the increase in the content of ettringite and monosulfide hydrated calcium aluminate in Example 1 was larger, while the increase in silicate clinker mineral reaction rate, bound water rate and cumulative heat release was lower than that in Comparative Example 1. This indicates that the hydration products of sulfoaluminate still participate in the subsequent strength formation of the green billet in Example 1, and the degree of silicate clinker reaction required for it to reach the cutting state and continue pre-curing is lower than that in Comparative Example 1.
[0090] Three unreinforced autoclaved aerated concrete products were randomly selected from the examples and comparative examples. After being placed in an environment with a temperature of 20±2℃ and a relative humidity of 50±5% for 7 days, specimens with dimensions of 100mm×100mm×100mm were cut from the middle of each group of samples. The dry bulk density and compressive strength were tested according to GB / T 11969-2020 "Test Method for Performance of Autoclaved Aerated Concrete", and the unit density strength was calculated based on the ratio of the two.
[0091] In addition, specimens with dimensions of 300mm×300mm×30mm were cut from each group of samples, and the thermal conductivity was tested using the protective hot plate method according to GB / T 10294-2008. Three parallel specimens were tested for each group and the average value was taken.
[0092] Specimens with dimensions of 40mm×40mm×160mm and a gauge length of 140mm were cut from each group of samples. The specimens were placed in an environment with a temperature of 20±2℃ and a relative humidity of 50±5% and their length was measured periodically until the length change between two consecutive measurements did not exceed 0.01mm. The drying shrinkage value was calculated based on the difference between the initial gauge length and the stable gauge length of the specimen. The test results are shown in Table 6.
[0093] Table 6 Physical properties of autoclaved products in each group
[0094]
[0095] As shown in Table 6, the dry bulk density of Examples 1-7 is 504-524 kg / m³. 3 The compressive strength is 3.91-4.34 MPa, and the density strength is 7.76-8.41 MPa·m. 3 The thermal conductivity is 0.117-0.122 W / (m·K), and the drying shrinkage is 0.39-0.47 mm / m. The overall performance is kept within a relatively concentrated range.
[0096] Example 1 has the highest unit density strength, and Example 5 has the highest compressive strength, but its dry bulk density and thermal conductivity are also relatively high. The unit density strength and drying shrinkage performance of Examples 4 and 6 have decreased, indicating that after the dosage of sulfoaluminate clinker and dihydrate gypsum deviated from that of Example 1, the increased dry bulk density failed to be converted into compressive strength in a synchronous manner.
[0097] Although Comparative Examples 2 and 4 achieved compressive strength close to that of some embodiments, their dry bulk density and thermal conductivity were higher, and their unit density strength was lower than that of the embodiments. The compressive strength and unit density strength of Comparative Examples 1, 3, and 5 decreased, and their drying shrinkage increased. This indicates that by controlling the amount and order of addition of sulfoaluminate clinker, gypsum dihydrate, and triethanolamine, the present invention can improve the load-bearing efficiency of the product and suppress drying shrinkage while maintaining a lower density and thermal conductivity.
[0098] Samples were taken from the middle of the same batch of finished plates used for testing in Table 6. The samples were crushed, vacuum dried at 40°C to constant weight, ground, and sieved through a 0.075mm sieve. The resulting powder was mixed with 10% α-Al₂O₃ internal standard. X-ray diffraction was performed according to the aforementioned conditions. The contents of tobermorite, residual quartz, hydrous garnet, and amorphous phases were calculated using the Rietveld full-spectrum fitting method. Three parallel samples were set for each group, and the average value was taken. The XRD patterns of the autoclaved products obtained in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 5 are shown in [reference needed]. Figure 3 .
[0099] A 100mm × 100mm cross-sectional sample was cut from the middle of the finished sheet material of the same batch, perpendicular to the pouring direction. After resin impregnation, grinding and polishing, the sample was scanned at high resolution. ImageJ software was used to identify and statistically analyze the images, calculate the proportion of pore area to the total cross-sectional area, and calculate the equivalent pore diameter of each pore according to the diameter of a circle with the same cross-sectional area. Based on this, the average equivalent pore diameter, the median pore diameter, and the coefficient of variation of pore diameter were determined. The coefficient of variation of pore diameter is the ratio of the standard deviation of pore diameter to the average equivalent pore diameter. Three cross-sections were tested in each group and the average value was taken. The test results are shown in Table 7.
[0100] Table 7. Main phase composition and pore structure of autoclaved products in each group
[0101]
[0102] As shown in Table 7, the tobermorite content of the examples is 28.1%-31.2%, the pore area ratio is 61.9%-64.4%, and the pore size variation coefficient is 0.46-0.56. Among them, Example 1 has a low pore size variation coefficient while maintaining a high pore area ratio. As shown in Table 6, it can balance low dry bulk density, thermal conductivity, and high density strength.
[0103] The tobermorite content of Comparative Examples 2 and 4 is similar to that of some of the embodiments, but the pore area ratio is lower, and the content of hydrated garnet and the coefficient of variation of pore size are higher. This indicates that the performance of autoclaved products is not only related to the tobermorite content, but also affected by the number of pores and the uniformity of pore size distribution.
[0104] The comparative examples 1, 3 and 5 had lower tobermorite content, higher residual quartz content and pore size variation coefficient, which correspond to the lower unit density strength and larger drying shrinkage in Table 6. This indicates that the regulation of the pre-curing stage reaction process in this invention is beneficial to the subsequent hydrothermal reaction and the formation of a uniform pore structure.
[0105] To investigate the effect of continued pre-curing after reaching the cutting state on the performance after autoclaving, Example 1 and Comparative Example 1 were selected, and two groups of parallel plate blanks were prepared respectively. One group was demolded and cut when the compressive strength of the green blank reached 0.30±0.02MPa. The other group was pre-cured for 60 minutes after reaching the same strength, and then demolded and cut. The plate blanks of each group were cured according to the aforementioned standards, cooled naturally after being taken out of the autoclave, and placed in an environment with a temperature of 20±2℃ and a relative humidity of 50±5% for 7 days.
[0106] Dry bulk density, compressive strength, thermal conductivity and drying shrinkage were tested, and the unit density strength was calculated. The content of tobermorite and residual quartz was also tested. Three parallel specimens were set up for each group and the average value was taken. The results are shown in Table 8.
[0107] Table 8 Autoclaving properties of the green body after 60 minutes of pre-curing
[0108]
[0109] As shown in Table 8, after Example 1 and Comparative Example 1 reached the cutting state, they continued to be pre-cured for 60 minutes. The dry bulk density of the autoclaved products increased slightly, while the compressive strength and unit density strength decreased. The tobermorite content decreased, and the residual quartz content and drying shrinkage increased. This indicates that continuing to extend the pre-curing time after the green blank reaches the cutting strength is not conducive to the subsequent hydrothermal reaction and the performance of the autoclaved products.
[0110] The performance change after continued pre-curing in Example 1 was less than that in Comparative Example 1. According to Table 5, the pre-curing strength of Example 1 is formed by the hydration products of sulfoaluminate and silicate, and has a low dependence on the continuous early reaction of ordinary silicate cement. Therefore, timely autoclaving after reaching the cutting strength is more conducive to maintaining the subsequent formation of tobermorite and the load-bearing capacity and volume stability of autoclaved products.
[0111] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A method for preparing a fly ash-based lightweight thermal insulation autoclaved aerated concrete panel, characterized in that, Includes the following steps: S1: Mix fly ash with water to prepare fly ash slurry; S2: Add quicklime, ordinary silicate cement and water to fly ash slurry and mix to obtain the main slurry; S3: The sulfoaluminate clinker and gypsum are pre-dry mixed. After the main slurry is formed, the resulting mixture is added to the main slurry, and a triethanolamine aqueous solution is added and mixed. The amount of triethanolamine, calculated as effective triethanolamine, is 0.20%-0.45% of the total mass of ordinary Portland cement and sulfoaluminate clinker. S4: Mix aluminum powder paste with water to prepare aluminum powder paste dispersion. After mixing in step S3, add aluminum powder paste dispersion to the slurry obtained in step S3, mix, and then pour into the mold. S5: Pre-cur the poured slurry. When the compressive strength of the green blank reaches 0.30MPa, demold and cut it to obtain the board blank. S6: The plate blank is steam-cured, removed from the autoclave and cooled to obtain the finished product.
2. The method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels according to claim 1, characterized in that: In step S1, fly ash and water are stirred at 600 r / min for 15 min to obtain fly ash slurry with a solid content of 56%-60%.
3. The method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels according to claim 1, characterized in that: In step S2, quicklime, ordinary silicate cement and water are added to the fly ash slurry and mixed at 900 r / min to obtain a main slurry with a temperature of 40-42℃ and a solid content of 62%-63%.
4. The method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels according to claim 1, characterized in that: In step S3, the triethanolamine aqueous solution has a mass fraction of 10%, which is obtained by diluting an 85% triethanolamine aqueous solution with water.
5. The method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels according to claim 1, characterized in that: In step S4, the aluminum powder paste is mixed with water at a mass ratio of 1:10 and stirred at 300 r / min for 2 min to obtain an aluminum powder paste dispersion.
6. The method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels according to claim 5, characterized in that: After the temperature of the slurry obtained in step S3 reaches 42±1℃, the aluminum powder paste dispersion is added and mixed at 600r / min. Then the resulting slurry is poured into the mold, with the initial pouring height being 53%-57% of the effective height of the mold.
7. The method for preparing fly ash-based lightweight thermal insulation autoclaved aerated concrete panels according to claim 1, characterized in that: In step S6, the plate blanks are grouped and sent into an autoclave. Steam is introduced to replace the air in the autoclave, and the temperature inside the autoclave is raised to 190±2℃ within 2 hours. The gauge pressure inside the autoclave is controlled at 1.15-1.25MPa and maintained at the temperature and pressure for 7 hours. Then, the pressure is reduced to atmospheric pressure within 2 hours. After the surface temperature of the product drops below 60℃, it is removed from the autoclave, separated, and naturally cooled to room temperature.
8. A fly ash-based lightweight thermal insulation autoclaved aerated concrete panel prepared by the preparation method according to any one of claims 1-7, characterized in that, The raw materials of the board, based on a dry basis of 100 parts, include 69.3-70.7 parts fly ash, 16.5 parts quicklime, 8.0-9.2 parts ordinary Portland cement, 0.8-2.0 parts sulfoaluminate clinker, and 2.8-4.2 parts dihydrate gypsum.
9. The fly ash-based lightweight thermal insulation autoclaved aerated concrete panel according to claim 8, characterized in that: The raw materials for the plate also include aluminum powder paste, the amount of which is calculated based on active aluminum, and the amount of active aluminum is 0.063% of the total dry basis.
10. The fly ash-based lightweight thermal insulation autoclaved aerated concrete panel according to claim 8, characterized in that: The dry bulk density of the board is 504-524 kg / m³. 3 Its compressive strength is 3.91-4.34 MPa, and its thermal conductivity is 0.117-0.122 W / (m·K).
Citation Information
Patent Citations
Autoclaved aerated concrete plate and molding process thereof
CN108585653A
Aerated concrete plate and manufacturing technology thereof
CN109650802A